IMPLEMENTATION of SDGs – 4 THROUGH DIGITIZATION OF EDUCATION AT SANGGAR BIMBINGAN KUALA LANGAT, SELANGOR, MALAYSIA - Madziatul Churiyah; Yuli Agustina; Heri Pratikto; Mohammad Arief; Eka Novianti Abdilah; Inneke Camelia N. C.; M. Habib Al Azhar; Moch. Yusufa Albar Bari'na (Transpublika Publisher, 2023)
Lecturers from Universitas Negeri Malang conducted Overseas Partnership Service activities at Sanggar Bimbingan Kuala Langat, Selangor, Malaysia. This service activity aims to enhance the quality of teaching and the understanding of both teachers and parents of students in the guidance studio, aligning with SDGs Goal 4, which is